Ownership Structure and Firm Financial Performance: Evidence From Panel Data in Sri Lanka - Wellalage , Nirosha Hewa; Locke , Stuart (Journal of Law and Governance, 2012)
This study investigates the effects of equity ownership structure on financial performance of Sri Lankan listed businesses. Using dynamic panel generalised method of moment this study finds an inverse hump shape relationship between insider ownership and firm financial performance. The results of this study confirm that the effect of insider ownership on firm performance is more positive and significant where legal protection for investors is weak. It suggests that although new legislative reforms have been enacted, Sri Lankan companies are highly dependent on internal governance mechanisms. There is potential merit in promulgating new rules to control the expropriation of minority shareholders.